2014
DOI: 10.1186/1477-7819-12-55
|View full text |Cite
|
Sign up to set email alerts
|

The impact of cyclin D1 overexpression on the prognosis of bladder cancer: a meta-analysis

Abstract: BackgroundTo evaluate the relationship between cyclin D1 overexpression and bladder cancer prognosis.MethodsA systematic literature search up to July 27, 2013 was carried out in PubMed and Wanfang databases, and the references of retrieved articles were screened. The hazard ratios (HRs) and their 95% CIs were used to combine the data. Heterogeneity and publication bias were also evaluated.ResultsA total of 15 studies containing 2,591 cases were included. We found that increased cyclin D1 levels were significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 32 publications
(21 reference statements)
0
18
0
1
Order By: Relevance
“…Cyclin D1 is a critical cell cycle regulatory protein, playing an important role in the G1/S transition through binding to cyclin-dependent kinase 4 (CDK4)to phosphorylate [23] and inactivate the retinoblastoma (Rb) protein [24]. Previous studies showed that increased CyclinD1 expression was associated with poor prognosis and decreased postoperative patient survival [25,26]. Additionally, a significant proportion of bladder cancer cases showed that over-expression of the c-Myc gene was relevant with bladder carcinogenesis as well [27][28][29].In this study, we detected Cyclin D1 and c-Myc expression levels under daidzein treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclin D1 is a critical cell cycle regulatory protein, playing an important role in the G1/S transition through binding to cyclin-dependent kinase 4 (CDK4)to phosphorylate [23] and inactivate the retinoblastoma (Rb) protein [24]. Previous studies showed that increased CyclinD1 expression was associated with poor prognosis and decreased postoperative patient survival [25,26]. Additionally, a significant proportion of bladder cancer cases showed that over-expression of the c-Myc gene was relevant with bladder carcinogenesis as well [27][28][29].In this study, we detected Cyclin D1 and c-Myc expression levels under daidzein treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Several meta‐analysis articles have explored the prognostic role of CCND1 in breast cancer, gastric cancer, bladder cancer, lung cancer, and oral squamous cell carcinomas . However, no meta‐analysis for CCND2 or CCND3 has been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…18 Although the data regarding the prognostic value of cyclin D1 is equivocal, a subgroup analysis in a study of 150 BCa patients revealed that over expression is considered as a predictor for lower progression rate and eventually better survival. 19 Cox’s multivariate analysis selected cyclin D3 as an independent predictor of progression-free survival together with tumor size in patients with Ta/T1 BCa. 20 A study of protein levels of cyclin E and p27 levels in BCa demonstrated significantly improved survival associated with low protein expression.…”
Section: Cell Cycle Regulatorsmentioning
confidence: 99%